Radioluminescence of silica optical fibre scintillators for real-time industrial radiation dosimetry. (November 2021) - Oresegun, Adebiyi; Basaif, A.; Tarif, Zubair H.; Abdul-Rashid, H.A.; Hashim, Siti Aiasah; Bradley, D.A.
Abstract: Dosimetry systems are important in any radiation facility to ensure quality, safety, validation, qualification and quality control of established and new processes, including at industrial radiation facilities. We present a study of silica optical fibre as scintillators for industrial radiation dosimetry using Radioluminescence (RL). The RL technique provides for a remote and real-time dosimetry measurement in such a high dose environment. This study establishes the dosimetric characteristics of two variants of pure silica optical fibre, low and high hydroxyl (OH) when exposed to industrial radiation levels. The samples were exposed to a linear accelerator, with doses in the order of tens of kGy (from 10 kGy through to 70 kGy in individual exposures). The performance parameters observed during the study include the RL emission spectrum, emission intensity and emission linearity with exposure dose. The RL spectrum demonstrated a central wavelength of 650 nm and 550 nm for the high and low OH scintillators, respectively. RL intensity was observed to increase with exposed dose, a result of recombination of ionizing radiation generated electron-hole pairs. The RL intensity relation with exposed dose indicated a linear response, with the higher OH sample showing the greater slope, indicating greater sensitivity. The overall results indicate the potential use of pure silica optical fibre as scintillators for remote and real-time industrial radiation dosimetry. Highlights: Real-time radiation dosimetry for industrial radiation using fiber optic coupled scintillators. Pure silica optical fiber scintillators. Higher sensitivity for high-OH pure silica fiber. Probe is intrinsically safe, and resistant to water and electromagnetic interference.